Graft-Free Sinus Augmentation Procedure: a Literature Review - Pinchasov, Ginnady (Stilus Optimus, 2014)
OBJECTIVES: The restoration of edentulous posterior maxilla with dental implants is challenging due to a deficient posterior alveolar ridge. Over the last decade an advance in the graftless bone augmentation procedures had occurred where the space left beneath the Schneiderian membrane is filled with blood clot in order to produce bone formation. The aim of present article is to review the scientific literature with respect to bone formation in the sinus, after membrane elevation procedure, without using any bone substitutes. MATERIAL AND METHODS: A comprehensive review of the current literature was conducted according to the PRISMA guidelines by accessing the NCBI PubMed database. The articles were searched from 1993 to 2013. English language articles with minimum one year patient follow-up and radiological and/or histological diagnostics of newly formed bone were included. Articles were excluded, if usage of bone graft or bone substitutes and/or usage of osteotome has been made during sinus lift operation. RESULTS: A total of 19 studies were included: 2 studies were related to the sinus membrane’s osteogenic potential, 3 to the histological evidence of bone formation in monkeys and humans, 12 to the radiologic evidence of bone gain, and 2 to the space-maintaining management. 100% of the reviewed articles presented with increased bone formation and high implant survival rates resulting from the graft-free technique. CONCLUSIONS: It is clearly shown in the review that the potential of the maxillary sinus to heal and to form new bone without bone grafts or substitutes is of high nature.